Business Development at Rumah Jahit Padang: Pengembangan Bisnis pada Rumah Jahit Padang - Indah Maya Sari; Berri Brilliant Albar (BULETIN ILMIAH NAGARI MEMBANGUN, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the fashion and tailoring industry often encounter managerial and operational challenges that hinder business sustainability and competitiveness. Rumah Jahit Padang, a home-based tailoring enterprise, faced several critical issues, including production bottlenecks, inconsistent service quality, inadequate financial management, and limited digital marketing practices. This community service program aimed to strengthen business governance through the implementation of an integrated management approach. A three-month intervention was conducted using the Participatory Action Research (PAR) approach, involving the business owner and three production staff. The intervention consisted of four key components: Business Model Canvas (BMC) development, Standard Operating Procedures (SOPs) formulation, financial management improvement, and digital marketing enhancement. Activities included diagnostic assessment, business process mapping, participatory workshops, hands-on mentoring, and post-intervention evaluation. The implementation of the program resulted in substantial improvements in operational and managerial performance. Production errors decreased by 32%, order fulfillment efficiency increased from 65% to 95%, and operational delays were eliminated through standardized workflows. Financial governance improved through the separation of personal and business finances and the adoption of structured bookkeeping practices. Furthermore, digital marketing initiatives expanded customer reach and enhanced the enterprise's online visibility. Overall, the integrated governance intervention successfully strengthened organizational capacity, improved service quality and operational efficiency, reduced business risks, and established a sustainable foundation for long-term MSME growth. The findings demonstrate that a holistic governance model combining strategic planning, operational standardization, financial management, and digital transformation can effectively enhance the competitiveness and resilience of small-scale tailoring enterprises.